OPTIMALISASI DISTRIBUSI PRODUK BBQ STREET DENGAN MENGGUNAKAN FOOD TRUCK - Imanuella Laviena (Universitas Ciputra Surabaya, 2016)
A developing company needs to optimize its primary distribution channels to ensure smooth product distribution to consumers. Food truck is the primary distribution channel for BBQ Street. The purpose of this research is to determine the potential areas for street vendors, the challenges and obstacles faced by street vendors that use food truck, and the ways to optimize BBQ Street's product distribution using food truck. This research is a qualitative research. Interview, observation, and documentation are used to collect research data. The subject of this study is BBQ Street in Surabaya, while the informants include food truck owners, food truck consumers, the city council of Surabaya, and Citraland officers. Research results suggest that all areas of Surabaya can be used by food truck sellers as long as parking and selling are not outlawed in the area. This research also recommends several potential selling areas for food truck sellers, including Citraland, Nirwana Residence, and Ubaya areas. Meanwhile the challenges for the food truck sellers are space and quota limitation in local areas, issues with the civil service police unit, and law uncertainty regarding food truck business. As for the distribution channel optimization, the company can employ a pull strategy by using Tenggilis Mejoyo area from Monday to Friday and the MERR area from Saturday to Sunday noon. Furthermore, when the development plan for Tunjungan area is completed, the company can also use the area from Saturday to Sunday evening.